Plano de gerenciamento de resíduos sólidos de serviços de saúde no Hospital Municipal de São Pedro do Sul – RS: um estudo de caso - Casado, Gessica Weber (2018)
Currently, it’s a major concern of the hospital managers and managers of the solid wastes from healthcare services. In order to promote the adequate management of this waste, each establishment is responsible for designing, implementing and monitoring the plan of healthcare wastes management. Therefore, the present study aims to implement the plan of healthcare wastes management at Hospital Municipal de São Pedro do Sul - RS, through the application of a spreadsheet of performance indicators to the management process of the healthcare wastes. In order to reach the proposed objective, a survey of the important indicators in the management process of healthcare wastes in the hospital was carried out, through bibliographical / documentary research, technical visits, on-site observations, photographic records, conversations with employees involved in management of healthcare wastes, and data collection. A spreadsheet with these indicators was then prepared and applied to the local reality from hospital. At the end, a spreadsheet with 55 indicators distributed in 8 categories was obtained. This spreadsheet incorporated the legal parameters and reflected the environmental performance of the health facility, highlighting more critical issues of the management system of the healthcare wastes at hospital, allowing strategic direction to improve actions. We also quantified the healthcare wastes production at hospital under study. It was found that Group D - Nonrecyclable waste contributed the most representativeness (71%), followed by Group A waste (16%), waste from the group D - recyclable (7%) and Group E waste (6%). Sensization activities were carried out on the management of healthcare wastes at to hospital professionals. Subsequently, a diagnosis was made of the level of knowledge about the healthcare wastes of the hospital professionals, through the application of semi-structured interviews, in two scenarios: Scenario I (before sensitization activities) and Scenario II (after sensitization activities). Before the sensitization activities, 78.57% of the professionals didn’t know if the hospital had a plan of healthcare wastes management, and 89.29% never had access to this document. These data demonstrate the importance of the hospital to implement a system of continuing education addressing the issue of management of healthcare wastes for all employees.